2019
DOI: 10.1126/sciadv.aaw8337
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen cluster doping for high-mobility/conductivity graphene films with millimeter-sized domains

Abstract: Directly incorporating heteroatoms into the hexagonal lattice of graphene during growth has been widely used to tune its electrical properties with superior doping stability, uniformity, and scalability. However the introduction of scattering centers limits this technique because of reduced carrier mobilities and conductivities of the resulting material. Here, we demonstrate a rapid growth of graphitic nitrogen cluster–doped monolayer graphene single crystals on Cu foil with remarkable carrier mobility of 13,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 62 publications
(86 reference statements)
9
42
0
Order By: Relevance
“…Note that indications of such an electron-hole asymmetry in electronic transport was reported in earlier work [115,118]. Finally, note that the same group has recently reported comprehensive results on nitrogen cluster doping [128]. Remarkably, compared to random doping, clustering allows higher mobility for similar electron doping.…”
Section: Magnetoresistance Experiments On Chemically-doped Graphenesupporting
confidence: 59%
See 1 more Smart Citation
“…Note that indications of such an electron-hole asymmetry in electronic transport was reported in earlier work [115,118]. Finally, note that the same group has recently reported comprehensive results on nitrogen cluster doping [128]. Remarkably, compared to random doping, clustering allows higher mobility for similar electron doping.…”
Section: Magnetoresistance Experiments On Chemically-doped Graphenesupporting
confidence: 59%
“…Remarkably, compared to random doping, clustering allows higher mobility for similar electron doping. This is explained by the concentration of the scattering sources around the dopants' clusters [128].…”
Section: Magnetoresistance Experiments On Chemically-doped Graphenementioning
confidence: 99%
“…DOI: 10.1002/adma.202002825 and conversion. It has been demonstrated that introducing dopants in 2D materials can improve the electrical conductivity and catalytic activity, [7,8] tune the bandgap and work function, [9,10] and introduce superconductivity and magnetism. [11,12] For the doped 2D materials, the properties are strongly depended on the doping species and concentration.…”
mentioning
confidence: 99%
“…The electron‐rich nitrogen functions as an electron donor by shifting the Fermi level of carbon species toward the valence band, thereby enhancing electrode conductivity [32] . In particular, graphitic or quaternary N‐Q sitting inside the six‐member ring with the least distortion in graphitic structure is the most efficient at increasing carrier mobilities [33] while N‐6, N‐5, and N‐X have been identified as surface redox centers that enhance the charge density [34] . A high doping level of 6.6 wt% is determined in the CN‐5 electrode.…”
Section: Resultsmentioning
confidence: 99%